ANALISIS PERHITUNGAN WAKTU STANDART UNTUK MENENTUKAN JUMLAH TENAGA KERJA OPTIMAL PADA PROSES PRODUKSI PT. NRZ PRIMA GASKET - Nevenda, Maria; Mei Cahya Wulandari, Lusi (Lafadz Jaya Publisher, 2024)
PT NRZ Prima Gasket is one of the companies engaged in manufacturing automotive parts. In the production process there is no standard time applied in the production process so that the company has not been able to determine exactly how much the number of labor needs should be according to the workload of each workstation. The author will use the standard time measurement method and the working time measurement method with the stopwatch method is expected to help the company in determining the target in making gasket production and to find out the optimal amount of labor for the implementation of production activities at the company so that the company will not obtain employee wages that are not optimal. In this study will use quantitative research. The qualitative approach is because the data collection carried out by researchers also uses interviews and observations, quantitative approach because the data processed is in the form of numerical data such as the time required for each element during the 6D16 gasket production process using Stopwatch. Based on calculations that have been carried out, the standard time for making 6D16 gaskets for 30 observations is 362.41 seconds and the working time is 420 minutes or 25,200 seconds or 7 hours per day. Then the optimum number of workers is 15 people. In accordance with the calculation of labor requirements with the workload method, the production section of type 6D16 gaskets, the number of employees to complete the work of making gaskets based on standard time and output targets, there is a waste of labor, where the number of workers used by PT. NRZ Prima Gasket is 17 people, while the optimum number of workers from the calculation only requires 15 workers.